Patient and Community Health Worker (CHW) Perspectives on a CHW-delivered Nutrition Intervention for Low-Income Adults with Hypertension: A Qualitative Study - Kristine D. Gu; Jessica Cheng; Ashlie Malone; Katherine C. Faulkner; Oldy Bejarano; Emily Gelsomin; Anne N. Thorndike (SAGE Publishing, 2024)
Introduction/Objectives: Adults with food insecurity (FI) face barriers to hypertension management, including difficulty adhering to diet recommendations. Few community health worker (CHW) interventions focus on diet to improve blood pressure. This qualitative study elicited patient and CHW perspectives on healthy eating and a future CHW nutrition intervention for patients with hypertension. Methods: Twenty-five patients with hypertension and FI and 5 CHWs participating in a hypertension health coaching program from 5 Boston-area health centers participated in semi-structured interviews from July to September 2023. Interviews were audio recorded, transcribed, and analyzed using the Framework Method. Results: Themes included: 1) Variable patient knowledge about dietary patterns for hypertension management and low confidence in interpreting nutrition labels; 2) Culture influenced healthy food perception; and 3) Barriers to healthy eating included cost, limited cooking abilities/supplies, and competing demands. Patients and CHWs favored simple nutrition education materials (e.g., traffic light nutrition ranking, healthy meals on a budget). Patients had mixed opinions about CHW-accompanied supermarket visits. Conclusions: This study identified culture, knowledge gaps, and budget constraints as factors influencing diet among patients with hypertension and FI. A CHW-delivered intervention could include simplified nutrition education, strategies for healthy eating on a budget, and linkage to community-based food programs.